Some reflections before the Beginning of the Research Project on Modern Natural and Technological Challenges in Russia - Yanitsky, Oleg (Advances in Social Sciences Research Journal, 2019)
The article represents an attempt of qualitative modelling of the organization and the process of work on the research project titled the ‘Volunteering in the Critical Situations as a Response to Natural and Technological Challenges in Russia’ taking into account the main impediments and difficulties generated by the inside and outside forces. Such attempt seems necessary because we launch this project in very uncertain conditions such as the transition period of Russia toward the Forth scientific and technological revolution (hereafter the STR-4), the prevalence of mono-disciplinary mode of the research and teaching as well as by a very waste territory of Russia with highly dispersed habitat, especially in the North, Siberia and the Far East. Only the triad as the ‘scientific knowledge—teaching—experience in situ’ could offer to the rescuers and volunteers a necessary knowledge and social experience, and our project have to be organized in a right way. Therefore, I suggest to launch the work on the project ‘from the end’ i.e. from the anticipated results of it in the form of one or several hypotheses related to the final results of the project. Such mode of collaboration of the project’s participants allows us to avoid a widespread mistake when the theoretical model of subject in question begins to contradict with the results of the following field-research.